Trained immunity in tuberculosis infection: a systematic review - Salma Rasiani; Beti Ernawati Dewi; Febriana Catur Iswanti (Indonesian Journal of Biomedicine and Clinical Sciences, 2026)
Tuberculosis (TB) is considered a major contributor to death resulting from pathogenic bacteria; specifically, Mycobacterium tuberculosis (Mtb) spreads through droplets from individuals with active TB. Both the innate and adaptive immune systems collaborate to control the infection, with innate immunity potentially playing a role in eliminating Mtb. Vaccination, early diagnosis, and treatment can reduce the severity of the infection, but new strategies are still needed to address TB. Research suggests that trained immunity may assist in combating pathogens, including Mtb, and could open new opportunities for treatment. A systematic review was conducted following the eight-step Cochrane methodology and adhering to PRISMA guidelines. An initial automated search identified 157 articles published between 2020 and 2025. Following duplicate removal and evaluation of titles and abstracts, 92 articles remained. After further screening, 52 articles were excluded, and 40 articles were identified for in-depth review. As a result, 8 publications satisfied all eligibility standards and were incorporated into the systematic review. Vaccines (e.g., BCG and TB-MAPS) and adjuvants (e.g., β-glucan) exploit trained immunity to enhance protection. BCG reprograms hematopoietic stem cells (HSCs) via chromatin remodeling, inducing long-term functional alterations in neutrophils, monocytes, and macrophages through epigenetic modifications (e.g., H3K4me3). TB-MAPS generated strong, long-lasting T cell and antibody responses and protected against Mtb infection in both lungs and spleen, matching BCG efficacy. When combined with BCG, it showed synergistic effects, further lowering lung bacterial load. Protection relied partly on IL-12p40 signaling, with IFN-γ and IL-17A pathways driving systemic and lung immunity. β-glucan operates via IL-1 signaling, epigenetically upregulating IL-1 family genes and enhancing proinflammatory responses via the PI3K/Akt/mTOR pathway. These interventions boost myelopoiesis and strengthen both innate and adaptive immune memory, providing stronger protection against TB and opening avenues for new therapeutic approaches.